Hyperspectral Imaging as an Early Biomarker for Radiation Exposure and Microcirculatory Damage - Chin, Michael S.; Freniere, Brian B.; Lancerotto, Luca; Lujan-Hernandez, Jorge; Saleeby, Jonathan H.; Lo, Yuan-Chyuan; Orgill, Dennis P.; Lalikos, Janice F.; Fitzgerald, Thomas J. (Frontiers in Oncology, 2015)
BACKGROUND: Radiation exposure can lead to detrimental effects in skin microcirculation. The precise relationship between radiation dose received and its effect on cutaneous perfusion still remains controversial. Previously, we have shown that hyperspectral imaging (HSI) is able to demonstrate long-term reductions in cutaneous perfusion secondary to chronic microvascular injury. This study characterizes the changes in skin microcirculation in response to varying doses of ionizing radiation and investigates these microcirculatory changes as a possible early non-invasive biomarker that may correlate with the extent of long-term microvascular damage. METHODS: Immunocompetent hairless mice (n=66) were exposed to single fractions of superficial beta-irradiation in doses of 0, 5, 10, 20, 35, or 50 Gy. A HSI device was utilized to measure deoxygenated hemoglobin levels in irradiated and control areas. HSI measurements were performed at baseline before radiation exposure and for the first three days post-irradiation. Maximum macroscopic skin reactions were graded, and histological assessment of cutaneous microvascular densities at four weeks post-irradiation was performed in harvested tissue by CD31 immunohistochemistry. RESULTS: CD31 immunohistochemistry demonstrated a significant correlation (r=0.90, p<0.0001) between dose and vessel density reduction at four weeks. Using HSI analysis, early changes in deoxygenated hemoglobin levels were observed during the first three days post-irradiation in all groups. These deoxygenated hemoglobin changes varied proportionally with dose (r=0.98, p<0.0001) and skin reactions (r=0.98, p<0.0001). There was a highly significant correlation (r= 0.91, p<0.0001) between these early changes in deoxygenated hemoglobin and late vascular injury severity assessed at the end of four weeks. CONCLUSIONS: Radiation dose is directly correlated with cutaneous microvascular injury severity at four weeks in our model. Early post-exposure measurement of cutaneous deoxygenated hemoglobin levels may be a useful biomarker for radiation dose reconstruction and predictor for chronic microvascular injury.